INTRACRANIAL PRESSURE MONITORING TECHNIQUE - Ida Bagus Adi Kayana; Sri Maliawan; I Ketut Siki Kawiyana (Universitas Udayana, 2013)
Head injury is the most significant cause of increased morbidity and mortality. An estimated 1.4 million head injuries occur each year, with and more than 1.1 million come to the Emergency Unit. On each patient head injury, an increase in intracranial pressure (ICP) related to poor outcomes and aggressive therapy to increased ICP can improve the outcomes. ICP monitoring is the most widely used because of the prevention and control of ICP as well as maintain the pressure increase perfusion of cerebral (Cerebral Perfusion Pressure/CPP) is the basic purpose of handling head injury. There are two methods of monitoring ICP that is an invasive methods (directly) and non-invasive techniques (indirectly). The method commonly used, namely intraventricular and intraparenkimal (microtransducer sensor) because it is more accurate but keep attention to the existence of the risk of bleeding and infection resulting from installation. Monitoring of ICT can determine the actions that avoid further brain injury, which can be lethal and irreversibel.